(untitled) (Research, Society and Development, 2022)
Chagas disease is a neglected tropical disease caused by the protozoan Trypanosoma cruzi. Currently only the drugs benznidazole and nifurtimox are used in the treatment of the disease. However, in addition to adverse effects, these drugs have reduced effectiveness, especially for chronic cases of the disease. A viable alternative is the investigation of new drugs from natural products. Catharanthus roseus is a common plant in tropical regions and has more than 130 terpenoids of relevant scientific interest. The present work aimed to investigate natural products in the prospect of new antichagasics drugs. In silico molecular docking were performed for 21 alkaloids derived from Catharanthus roseus in the active site of cruzain, the main cysteine ​​protease of Trypanosoma cruzi. The main results demonstrated the formation of enzyme complexes of considerable stability for the compounds strictosidine (ΔG = -11.23 Kcal.mol-1), ajmalicine (ΔG = -9.59 Kcal.mol-1) and serpentine (ΔG = - 9.28 Kcal.mol-1). These results demonstrated a good enzyme inhibitory activity of cruzain. ADMET and PASS predictions showed promising results for absorption rates and bioavailability. Therefore, the investigated molecules were considered promising in the prospect of new anti-chagasic drugs.